Analisis Pengaruh Pengalaman Merek Dan Electronic Word Of Mouth Terhadap Loyalitas Merek Dengan Kepuasan Merek Dan Kepercayaan Merek Sebagai Variabel Intervening: Studi Pada Konsumen Produk Wardah Glasting Liquid Lip - Frida Laksiasti; Idris Idris (Faculty of Economics and Business Diponegoro University, 2026)
This study examines the effects of Brand Experience and electronic word of mouth on brand loyalty among Wardah consumers in Semarang City, Indonesia. Although the Indonesian cosmetic industry has grown rapidly and competition between local and global brands has intensified, Wardah still faces challenges in maintaining consumer loyalty despite its halal positioning. Using a quantitative approach, data were collected through questionnaires distributed to 160 respondents and analyzed using SEM with SmartPLS 4.0. The results show that Brand Experience and electronic word of mouth do not only influence Brand Loyalty directly, but also indirectly through Brand Satisfaction and Brand Trust. In addition, Brand Satisfaction and Brand Trust significantly mediate the relationship between the independent variables and Brand Loyalty. These findings highlight the important role of positive consumer experiences, electronic information, satisfaction, and trust in strengthening brand loyalty.